Training and technical assistance program for the development of small and medium enterprise (SMEs): A study of Bumiputera entrepreneurs in Kedah state of Malaysia - Abdullah, Syahrina; Mohamed, Armanurah (Universiti Malaysia Sarawak, 2005)
The issue of 'knowledge based society' in the small business sector in Malaysia has been rising on discussion among the academician and policy maker in emerging economics. Many studies have shown that knowledge and skills plays a vital role for small business development. Furthermore, the government support in term of 'Training and Technical Assistance Program' when dealing with small business can be considered very important for business growth and development. In many countries, the essential and greater important contribution of SMEs for economic development is widely recognized. Since the contribution of the SMEs has been acknowledged, the lack on issues of knowledge and skills of SMEs give a constraint towards achieving success and growth. The purpose of this study therefore to contribute an understanding the importance of training and technical assistance for SMEs development in the state of Kedah, Malaysia. To increase the credibility of this study, a further research on similar issues has been suggested.